On the exploration and exploitation in popular swarm-based metaheuristic algorithms - Hussain, Kashif; Mohd Salleh, Mohd Najib; Cheng, Shi; Shi, Yuhui (Springer, 2018)
It is obvious from wider spectrum of successful applications that metaheuristic algorithms are potential solutions to hard optimization problems. Among such algorithms are swarm-based methods like particle swarm optimization and ant colony optimization which are increasingly attracting new researchers. Despite popularity, the core questions on performance issues are still partially answered due to limited insightful analyses. Mere investigation and comparison of end results may not reveal the reasons behind poor or better performance. This study, therefore, performed in-depth empirical analysis by quantitatively analyzing exploration and exploitation of five swarm-based metaheuristic algorithms. The analysis unearthed explanations the way algorithms performed on numerical problems as well as on real-world application of classification using adaptive neuro-fuzzy inference system (ANFIS) trained by selected metaheuristics. The outcome of empirical study suggested that coherence and consistency in the swarm individuals throughout iterations is the key to success in swarmbased metaheuristic algorithms. The analytical approach adopted in this study may be employed to perform componentwise diversity analysis so that the contribution of each component on performance may be determined for devising efficient search strategies.